HUBUNGAN PERSEPSI KESELAMATAN DAN KESEHATAN KERJA DENGAN PERILAKU K3 PADA PEKERJA BAGIAN PRODUKSI PT. SUMPRATAMA JURU ENGINEERING MEDAN TAHUN 2015 - nur agustia kerinci; namora lumongga lubis; arfah mardiana lubis (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACTOccupational Health and Safety is a work in order to safeguard workers are always in safe and healthy workplace for doing the job. K3 must be implanted in the workers themselves in order to have a good perception of the K3 and safe behavior at work.This research was conducted at production workers. PT. Sumpratama Juru Engineering Medan in 2015 to find out how much the correlation between perception on K3 and their behavior in K3 on workers. Type of analytical research using cross sectional design. Total population 63 production section consists of 4 units, 25 person panel unit, 10 person painting unit, 20 person wiring unit, and 8 person quality control, a sample of 39 people, sampling using simple random sampling technique taken from the 4 units. Data was collected by interview using a questionnaire to determine the worker's perception and observation using observation sheet to determine the behavior of workers. To know the great correlation between independent variables with the dependent variable Spearman statistical test.Research results obtained, category K3 safe behavior was found in both categories of perception as much as 19 people (48.7%), lack of perception as much as 4 people (10.3%). Meanwhile, the K3 categories unsafe behavior found in the perception of both categories of 7 people (17.9%), and lack of perception as much as 9 people (23.1%). The test results obtained statistically significant correlation between the perception of health and safety with the behavior of K3 P-value = 0,010, and the magnitude of correlation between perception of health and safety with K3 behavior (r) = 0.405, the value of (r) showed a moderate and patterned positive. This means that the better the perception of safety and health then the better the behavior of workers K3.